Action Research on error treatment and feedback session in Oral Expression: Language III at a Tertiary Teacher Training College in Mar del Plata City, Argentina - Ferreiro, Gabriela Mariel; Moreno Trillo, Valeria Andrea (Didáctica. Lengua y Literatura, 2016)
Action research is a valuable tool which helps to reconstruct the teaching practice since it connects research, action and professional development. This research paper intends to explore error treatment and its subsequent feedback session in the subject Oral Expression: Language III at Tertiary Teacher Training College IDRA, located in Mar del Plata, Buenos Aires, Argentina. Two research professors and 18 students attending this subject participated in this investigation. Having identified the aims of the research - to examine error treatment and subsequent feedback session - and the need to optimize both instances, substantial changes were implemented in the classroom practice, especially in practical assignments and term tests. Before the end of the academic year the students were administered a questionnaire to reflect upon the innovations being introduced. Analysis of results suggests that the use of recordings, transcriptions and subsequent self-correction fostered reflection and awareness raising among the participants and their oral production. In like manner, this procedure also benefitted the feedback session turning it into a more dynamic experience.